Development of 3D Page Flip Physics E-Module with Sound Wave Material Based on Local Angklung Wisdom to Improve Integrated Science Process Skills - Nartiya, Nartiya; Ilmiah, Paridatul; Kedkaew, Chittra; David, Andrew (Schrödinger: Journal of Physics Education, 2022)
Purpose of the study: The research objective of developing the 3D Pageflip Physics E-Module with sound wave material based on local angklung wisdom is to increase students' understanding of physics concepts, integrate local cultural values as a learning context, and develop students' science process skills in an integrated manner. Methodology: The research method used in this research is the research and development. Respondents the e-module consisted of 20 class XI Science. The data collection technique is a questionnaire. The data analysis technique uses descriptive statistical tests, expert validation tests to determine feasibility e-module. The research procedure is by conducting literature studies, planning, development, product validation, revision, small group testing. Main Findings: The research results show that the physics e-module with West Java local wisdom on Sound Waves material has been successfully developed. Validation from experts results in positive assessment of the material content, media and language the module. Students' responses to small-scale test showed good level of acceptance, as well as an increase in their understanding of physics sound concepts. Thus, this e-module has potential to improve physics learning at the high school level, especially in the local context West Java. Novelty/Originality of this study: The new thing here is integrating scientific skills with the use of the traditional angklung musical instrument. Embracing the local wisdom of angklung, this e-module offers dynamic and relevant learning, helping students understand physics concepts while comprehensively improving science process skills.